Antibiotics Use in Dental Practice: A Review - Basanta Kumar Choudhury1, Suvranita Jena2, Sanat Kumar Bhuyan3, Rajat Panigrahi4, Abhishek Ranjan Pa (Indian Journal of Forensic Medicine & Toxicology, 2020)
In dentistry, indications of antibiotics are determined by multiple clinical and bacteriological epidemiologicalfactors. Treating odontogenic and non-odontogenic infections, for local infections, anti-microbial coverageis recommended. These act as an adjunct to dental treatment. The paper reviews the indications, usage,dosage of antibiotics, precautionary measures to be taken while prescribing them.